Synergistic effects of aloe vera and moringa oleifera in chitosan-based composites for preservation of banana fruit - Nor Hanuni, Ramli; Olunusi, Samuel Olugbenga; Tuan Basyirah, T. Z.; Adam D., Ahmad-Kamal; Nursyahirah, Mat Nawi; Norhafezah, Kasmuri; Ahmad F.H., Ismal (AIDIC Servizi, 2024)
Chitosan, derived from deacetylated chitin, is renowned for various industrial applications, including fruit coatings, due to its distinct biological and physicochemical properties such as film-forming capability, biodegradability, non-toxicity, biocompatibility, and antimicrobial attributes. Chitosan exhibits certain limitations, including hydrophilicity, low mechanical strength, and poor mass transfer barriers. This research leveraged chitosan's biocompatibility by using sodium tripolyphosphate (NaTPP) as a crosslinker to strengthen chitosan (CH) molecules via ionic gelation, with Tween 80 as an emulsifier. Adding Aloe vera (AV) and Moringa oleifera (MO) to the chitosan-NaTPP coating solution aimed to further limit the respiration rate and inhibit microorganism proliferation. The study examined the physicochemical stability and characteristics of chitosan-NaTPP coating solutions with varying concentrations of AV, MO, and both. The effect of the deposition method, including single and double layers, on banana fruit was also studied over 10 d of storage. The particle size was characterized using Malvern Zeta Sizer Nano ZS and chemical bonding of the coating solutions using Fourier Transform Infrared Spectroscopy (FTIR). The particle size of the CH-NaTPP coating solution was 3.2 nm, CH-NaTPP/AV was 3.6 nm, CH-NaTPP/MO was 3.1 nm, and CH-NaTPP/AV/MO was 2.7 nm. Bananas coated with CH-NaTPP containing 1 % AV and 3 % MO exhibited the slowest ripening process during 10 d of storage. In conclusion, the formulated CH-NaTPP/1 % AV/3 % MO composite proved effective for fruit coating applications, particularly for bananas.